Babushka : a Christmas tale - Casey, Dawn, 1975- (Good Books, 2016)
"With beautiful illustrations evoking folk art traditions and sensitive storytelling, Babushka tenderly reminds us that nothing is more important during the holiday season than taking the time to show love for one another. This timeless Russian tale will warm your heart and fill you up with the joyful, generous spirit of Christmas"--Amazon.com.